Effect of Nitrogen and Phosphorus Distribution in Overlying Water and Sediment of Major Rivers in Changchun City on Water Quality - Xiaodan Tang; Zhenghe Li; Shan He; Binghan Yang; Zeyu Zhang; Bing Li; Yuyan Zhao (Applied Sciences, 2022)
To explore the existing characteristics of nitrogen and phosphorus in the main rivers of Changchun City, the overlying water and sediment were sampled and tested. The results showed that the spatial distribution of nitrogen and phosphorus contents in overlying water and sediment was diverse. In overlying water, nitrogen and phosphorus contents in the north and west of Changchun were high, while their contents in the south were low. In the sediment, their contents were high in the south and west and low in the north. The pollution of nitrogen and phosphorus was serious in most rivers. Xinkai River, Chuan Lake, and West Lake had the acutest pollution of ammonia, total nitrogen, and total phosphorus, and their contamination degree in Yongchun River was the lowest. In terms of time, with the government actively carrying out river management, the pollution control of ammonia and phosphorus has achieved remarkable results. The pollution of nitrogen and phosphorus was closely related to the quality of the water environment, and the phosphorus content in overlying water and sediment had the strongest correlation with other water quality parameters. Moreover, the change in chemical oxygen demand could be predicted by the partial least squares method on the basis of its high correlation with nitrogen and phosphorus in overlying water. This study provides a scientific reference for the investigation and treatment of nitrogen and phosphorus pollution in surface water of typical old industrial cities in China.